Introduction to advertising : understanding and managing the advertising process - Mogaji, Emmanuel (Routledge, 2021)
"This book is an introductory roadmap to the advertising process. Advertising is explored as a creative communication message from a brand, created by advertising agencies and distributed across different media to target the right consumers. The book provides an understanding of the benefits of advertising, its role in the economy, and even more so acknowledges that advertisements are not all about selling but are also about effectively communicating a message. The creative and conceptual approach towards the communication process is discussed, and insight is presented into the dynamics within the industry and the different stakeholders involved, while recognising how different creative elements in advertisements are consciously selected to make them appealing. Finally, it considers how to analyse and measure an advert's effectiveness and looks ahead to future ideas and technologies arising in advertising. Effectively combining theory with practical insight, each chapter begins with learning objectives and ends with key learnings. International case studies feature throughout, including insights from British Gas, WPP, Audi and KFC, as well as other examples from smaller organizations and the non-profit sector. Taking students step by step through the advertising process, it is important reading for undergraduate and postgraduate students studying Advertising, Brand Management, Marketing Communications and Media Planning"--